Students’ Writing Anxiety and Its Correlation to Their Writing Achievement - Rizki Annisa; Ridha Ilma; Renny Kurniasari (Didascein : Journal of English Education, 2024)
Writing plays an important role in learning and understanding English. Students consider writing difficult due to writing anxiety and lack of confidence. This study aimed to investigate the correlation between students' writing anxiety and their writing achievement. The sample consisted of thirty-three students from one of the senior high schools in Prabumulih, South Sumatra. A correlational study was used to design the study. A questionnaire and reading comprehension test were the instruments to collect the data. Based on the findings, the majority of the students, specifically 61%, exhibited symptoms of physical anxiety. Additionally, a smaller proportion of students, namely 9%, displayed signs of avoidance anxiety, while cognitive anxiety was reported by 30% of the participants. Researchers found that 5 students (15%) on the critical exposition test were considered average, 3 students (9%) were considered fair, 6 students (18%) were considered poor, and 19 students (58%) were considered inadequate. The study found a significant correlation (sig.2-tailed) of 0.30 between students' writing anxiety and their writing achievement. With coefficients of 0.104, cognitive anxiety emerged as the most common form of writing anxiety among students. This finding indicated that cognitive anxiety was responsible for the greatest contribution to students' writing achievement.